Faktor-Faktor Yang Mempengaruhi Purchase Intention Pada Pengguna Aplikasi Blibli Di Jakarta - Utami, Alifa Aulia (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2026)
This study set out to determine how perceived usefulness, perceived risk, and perceived ease of use on the Jakarta BliBli application affected consumers' intentions to make a purchase. The 5-point Likert scale was used to measure each variable in this study, which incorporated descriptive and causal research in its design. This study uses both primary and secondary data, and questionnaires were utilized to gather the information. The research sample, which comprised 200 respondents, was assembled via purposeful sampling. The testing tool employed in this study's statistical technique is SMARTPLS 3.3. The study's findings show that the variables for perceived usefulness, perceived ease of use, perceived ease of use, perceived risk, and perceived usefulness all have an impact on the purchase intention variable.